Chemical and Microbiological Properties of Buduk, A Commercial Fish Sauce from West Kalimantan - Risa Nofiani; Endang Elminah; Puji Ardiningsih (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Buduk is a fish sauce prepared by fermenting fresh small fish with various ingredients such as sugar,roasted rice, vinegar or wine. This study was aimed to assess the physicochemical and microbiologicalproperties of commercial buduk in the Province of West Kalimantan. The Buduk had pH 5-55, moisture52.35%, salt 1.96%, titrated acid 10.80%, free amino nitrogen 1.83 mmol/g, free fatty acid 17.96%, ethanol0.95%, total of mesophilic bacteria 4.81 log CFU/g and lactic acid bacteria 2.09 CFU/g, but no pathogenicbacteria detected. Each commercial buduk showed different physicochemical properties probably causedby variation in recipe of each producer. The microbiological properties did not significantly different but theTMAB found more than the threshold value indicating